Comparability of serum folate concentration measured by a microbiological method, LC-MS/MS and immunoassay - Sarah Meadows; Amanda McKillion; Damon A Parkington; Albert Koulman; Kerry S Jones (Annals of Clinical Biochemistry: International Journal of Laboratory Medicine, 2026)
Background Folate, vitamin B9, is an essential micronutrient for DNA replication and repair. Deficiency is associated with megaloblastic anaemia and fetal neural tube defects. Serum folate measurement provides a convenient biomarker of folate status in clinical and research settings. The overall aim of this evaluation was to compare serum folate results measured from three different technologies within the same laboratory to determine systematic biases and equivalence between methods. Methods 58 serum samples from the UK National Diet and Nutrition Survey were used to compare a microbiological method, a liquid chromatography tandem mass spectrometry method (LC-MS/MS) and a commercial immunoassay (Tosoh CL1200). Results Within-run imprecision of all three assays was ≤7%, measured at two concentrations. The microbiological and LC-MS/MS methods were accurate against NIST Standard Reference Material and VITAL External Quality Assessment (EQA) target values. The plasma-based sample used for the NIST Standard Reference Material (SRM) was unsuitable for analysis by the Tosoh immunoassay, however comparison with the VITAL EQA target values showed good accuracy. Using the serum samples, both the LC-MS/MS and Tosoh immunoassay methods showed a slight positive proportional bias compared to the microbiological method, whilst the Tosoh method also had an additional constant bias of 3-4 nmol/L compared to the other methods. Conclusions This data shows that the microbiological method, LC-MS/MS and Tosoh CL1200 immunoassay have acceptable accuracy, imprecision and agreement. The small concentration dependant bias is likely explainable by the expected characteristics of the individual methods and ability to detect and respond to different forms of folate.